1984
DOI: 10.1159/000123969
|View full text |Cite
|
Sign up to set email alerts
|

Median Eminence Serotonin Involved in the Proestrus Gonadotropin Release

Abstract: Numerous studies have suggested that serotonin (5-HT) is involved in the regulation of anterior pituitary hormone release. In the present study, the 5-HT concentrations of the median eminence and anterior pituitary lobe were measured during the estrous cycle and lactation in order to correlate changes in 5-HT levels with changes in serum luteinizing hormone, follicle-stimulating hormone, and prolactin. On the day of proestrus, median eminence 5-HT concentrations declined significantly between 14.00 and 16.30 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
14
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…The DR has a serotonergic projection to the ME [20] and ME-5-HT content has been described to decrease in the af ternoon of proestrus [22]. The present report shows that after DR lesion, 5-HT in the ME drops by about 50%: in these animals 5-HT does not further decrease during proestrous afternoon.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…The DR has a serotonergic projection to the ME [20] and ME-5-HT content has been described to decrease in the af ternoon of proestrus [22]. The present report shows that after DR lesion, 5-HT in the ME drops by about 50%: in these animals 5-HT does not further decrease during proestrous afternoon.…”
Section: Discussionsupporting
confidence: 43%
“…However, recently, a stimulatory role of 5-HT on preovulatory gonadotropin release at the level of the hypo thalamus has been suggested [6,25,26]. The decline of 5-HT content and the increase of 5-HT turnover in the median eminence (ME) in the afternoon of proestrus led us to propose the ME as a site where this stimulatory influence takes place [22]. This assumption was supported by an in vitro approach in which the addition of 5-HT to perifused ME from proestrous rats significantly increased LH-RH re lease [23,24].…”
mentioning
confidence: 99%
“…Others have suggested that the dual effect of 5HT is due to its exerting opposite effects at different sites. Recent evidence based on changes in 5HT turnover indi cates that the POA and ME are sites for the stimulatory action of 5HT on LH release [6,22,25,48,50] while it is inhibitory to both gonadotrophin release and sexual behaviour in the ARC [9,12] and the VMN [10,21,22], Alternatively, these dual effects may reflect the activation of different 5HT recep tors. Indeed, there is some evidence that 5HT is inhibitory to female sexual behaviour via 5HT| receptors and stimulatory via 5HT: receptors [2,32,33,55].…”
Section: Discussionmentioning
confidence: 99%
“…The responsiveness of each neurotransmitter system to gonadal steroids in conjunction with its specific 1 A preliminary report of this work was given at the Society for Neuroscience Annual Meeting, Anaheim, California, October 10-14, 1984. Received: February 6, 1985 Accepted after revision: May 9, 1985 function in a given area of the hypothalamus and related brain areas is thought to provide the necessary mechanism through which these steroids modify numerous reproduc tive functions from sexual behavior to ovujation [31].Changes in 5-hydroxytryptamine (5HT; serotonin) con centrations [28, 29,38,45], 5HT| receptor binding [4] and 5HT uptake [32] have been demonstrated in various brain regions including the hypothalamus during the course of the estrous cycle in rats and mice. Concurrent with the surge in serum LH levels following the sequential adminis tration of estradiol (E^) and progesterone (P) to ovariecto mized rats [25,41], an increase both in 5HT concentration and 5HT synthesis is seen in the dorsal raphé nuclei [8].…”
mentioning
confidence: 99%